2016
DOI: 10.3233/jcb-15023
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein IIB-IIIA inhibitor, monafram decelerate the early phase of red blood cells aggregation

Abstract: It is commonly known that red blood cell (RBC) tendency to reversibly aggregate contribute to the unique flow properties of blood. The fibrinogen-induced aggregation is primarily based on non-specific processes. Nevertheless, recent investigations disclosed a possibility of the specific fibrinogen-RBC binding, however, its role in RBC aggregation remains unclear. We conducted a study to determine whether this specific interaction is essential for natural RBC aggregation. The influence of glycoprotein (GP) IIb-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…The possibility of fibrinogen binding to RBCs is supported by a number of other studies, as noted in the introduction. 20,23,33,34 Our measurement results of the disaggregation process cannot be explained by the increasing effective interaction area while the linear overlap A between RBCs is decreasing because of the biconcave shape of the cells. RBCs are expected to reach a maximum interaction area at approximately A ¼ 3.5 μm, at which point the effective interaction area is at a maximum, and then should start to decrease.…”
Section: Fibrinogen-induced Red Blood Cell Aggregationmentioning
confidence: 73%
See 2 more Smart Citations
“…The possibility of fibrinogen binding to RBCs is supported by a number of other studies, as noted in the introduction. 20,23,33,34 Our measurement results of the disaggregation process cannot be explained by the increasing effective interaction area while the linear overlap A between RBCs is decreasing because of the biconcave shape of the cells. RBCs are expected to reach a maximum interaction area at approximately A ¼ 3.5 μm, at which point the effective interaction area is at a maximum, and then should start to decrease.…”
Section: Fibrinogen-induced Red Blood Cell Aggregationmentioning
confidence: 73%
“…Therefore, the RBC interaction mechanism in protein solutions and plasma should be considered still unclear. 20,21,23,33,34 In particular, the RBC disaggregation kinetics obtained using OT appear to require a different interpretation from those predicted by existing interaction models.…”
Section: Red Blood Cell Interaction Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…We divided each of the groups into subgroups in correspondence with the earlier developed criterion [19]: the indices of RBC aggregationand disaggregation being within 95% confidence interval for their normal values, which is a sign of normal aggregation (Nn, n = 19; DM1n, n = 8; DM2n, n = 5), or beyond these limits, which is a sign of "hyperaggregation" (Nh, n = 12; DM1h, n = 11; DM2h, n = 7). The analysis revealed that in the case of normal aggregation-disaggregation dynamics monafram still affected only t 1 , increasing it in all subgroups by 5%-20%.…”
Section: Effect Of Monafram On the Processes Of Rbc Aggregation In Pamentioning
confidence: 99%
“…These data showed that the specific fibrinogen-RBC binding only slightly accelerated the cell interaction, which could facilitate the appearance of positive consequences of the normally reversible red blood cells aggregation. On the contrary, in the case of "hyperaggregation" (as a rule, transitory in the normal state) the specific interaction of fibrinogen with the RBC membrane could facilitate abnormal phenomena, related to the accelerated formation of cell aggregates having increased stability [11,19].…”
Section: Effect Of Monafram On the Processes Of Rbc Aggregation In Pamentioning
confidence: 99%